Upland Rice Tolerance Test Based on Pissy Seeds on Ultisols Used for Cultivation of Bulbs and New Openings - Yandro Yandro Pratama; Widodo Haryoko; M. Zulman Harja Utama (Fakultas Pertanian Universitas Muara Bungo, 2022)
Upland rice tolerance test trials based on pithy seeds on ultisols used for tuber cultivation and new openings were carried out from November 2019 – February 2021 in Nagari Kampung Pinang, Lubuk Basung sub-district with the aim of knowing the interaction of upland rice varieties on ultisols of former tubers and new openings of ultisols. This experiment was conducted in a factorial Randomized Block Design with two factors. The first factor was the upland rice varieties Rindang I, Luhur I and Barabah, and the second factor was the ultisol treated layer, namely cassava ultisol, onion ultisol treatment layer and new layer processing. Based on the experiment, it was concluded that the three upland rice varieties tested, namely Rindang I, Luhur I and Barabah were classified as tolerant varieties with the order of tolerance being the Rindang I variety, followed by the Luhur I variety and the Barabah variety. Keywords: rice, ultisol, cassava, shallot